Economic analysis: a study case of Jatropha curcas L. using the partial budgets methodology - Ávalos-Cerdas, Juan Manuel; Villalobos-Monge, Alexis (Agronomía Mesoamericana, 2018)
The methodology of partial budgets is an important form of economic analysis that contemplates that the costs between different agricultural trials differ without having to arrive directly to the production site, a fact that does not always happen on this type of experiments. The objective of the present work was to perform an analysis by means of partial budgets, in an experimental plot of Jatropha curcas. The experiment was carried out at the Fabio Baudrit Moreno Agricultural Experiment Station, La Garita, Alajuela, Costa Rica, between January and August,2014. An evaluation of the effect of five products against Polyphagotarsonemus latus on Jatropha curcas plants was performed,this products are:hexithiazox (1 ml/l of water), sulfur (10 kg/ha),propargite (4 kg/ha),spiromesifen(0.5 l/ha) and abamectin (1.5 l/ha). Two products applications were carried out, each application happened twenty-two days apart. After each application, the number of mites (eggs, larvae and adults) present on each treatment was evaluated. The methodology of partial budgets was used with an adjustment in order to determine which treatment from an economical point of view was the best. The results indicated that the treatment with the best cost-benefit ratio was abamectin with MRT values (marginal rate of return) of 17.1%, 4.6%, and 4.1%, for eggs, larvae and adults, respectively; followed by spiromesifen with a TRM for eggs of 5%, larvae of 1.8%, and adults of 3.8%, and finally sulfur; according to the TRM analysis. This indicates that the product with the lowest cost is not necessarily the product with the best results.